Comparative Study of Electoral Systems, 2001-2006 ... : Archival Version ... - Sapiro, Virginia; Shively, W. Philips (ICPSR - Interuniversity Consortium for Political and Social Research, 2004)
This study is the full release of 2001-2006 data from Module 2 of the Comparative Study of Electoral Systems. The Comparative Study of Electoral Systems is an ongoing collaborative program of crossnational research among national election studies designed to advance the understanding of electoral behavior across polities. The project, which is being carried out in over 50 consolidated and emerging democracies, was coordinated by social scientists from around the world who cooperated to specify the research agenda, the study design, and the micro- and macro-level data that native teams of researchers collected within each polity. This collection currently comprises data from surveys conducted in the countries of Albania, Australia, Belgium, Brazil, Bulgaria, Canada, Chile, Czech Republic, Denmark, Finland, France, Germany, Great Britain, Hong Kong, Hungary, Iceland, Ireland, Israel, Italy, Japan, Kyrgyzstan, Mexico, Netherlands, New Zealand, Norway, Peru, Philippines, Poland, Portugal, Romania, Russia, ... : The CSES Module 2 Full Release includes original weight data (variables B1010_1, B1010_2, and B1010_3), as provided by the collaborators, where available. The weight variables provided by the collaborators vary greatly because of the variance in the sample designs used in the election studies included in this project. Most election studies provided at least a single weight in one of three categories (sample, demographic, political), although some countries did not provide a weight at all. The remainder of the weight variables are derivatives constructed from the original weights by CSES. Analysts are advised to read the weight documentation carefully to ensure that their analyses are weighted appropriately. ...